Health risk analysis of microplastics in soil in the 21st century: A scientometrics review - Sun, Yitao; Yang, Chao; Liang, Huajun; Zhang, Siqi; Zhang, Ruifang; Dong, Yongli; Tanveer, Sikander Khan; Hai, Jiangbo (Frontiers in Environmental Science, 2022)
Microplastics (MPs) in soil cause severe damage to the ecological environment and organisms, and research on their health risks has received extensive attention, but there is no comprehensive review of this research. From the perspective of bibliometrics, this paper systematically and comprehensively describes the progress, trends, and hotspots of health risks of MPs in soil based on the Web of Science Core Collection, Pubmed, and Scopus databases. Since 2016, people’s research on the health risks of MPs in soil has increased yearly; MPs in soil mainly come from Plastic mulch, Plastic waste, Sludge and sewage, and Organic fertilizer. China has the most publications on the health risks of MPs on soil, and more than half of the top 10 institutions with active publications in this field are from China. This paper systematically expounds on the health risks of MPs to organisms (plants, humans, and microorganisms) and control measures. Cooperation between different countries/institutions and fields/disciplines on the health risk analysis of MPs in soil and research on more efficient, green, and environmentally friendly methods and technologies for reducing soil MPs content will become the frontier trends of future development which provide valuable reference and help for future researchers.